(untitled) (Research, Society and Development, 2025)
Non-melanoma skin carcinomas (NMSC), mainly represented by basal cell carcinoma (BCC) and squamous cell carcinoma (SCC), are the most prevalent malignant neoplasms in humans, with a steadily increasing global incidence. Although they present low lethality, their high morbidity associated with local tissue destruction and recurrence requires strict clinical attention. Among the etiological factors, exposure to ultraviolet radiation stands out, especially in fair-skinned individuals, immunosuppressed patients, or those with genetic predisposition. Selecting an appropriate therapeutic approach is essential for disease control, and in this context, surgical treatment remains the gold standard. Thus, this article aims to analyze the aspects and surgical approaches of non-melanoma skin carcinomas. Thus, this study is configured as a qualitative review of the bibliographic review type and the specific type of narrative review, carried out through a bibliographic survey in the directories Google Scholar and Scientific Electronic Library Online (SciELO), using the Health Sciences Descriptors (DeCS) and Medical Subject Headings (MeSH) in both Portuguese and English. The following terms were used: “non-melanoma skin,” “surgery,” and “treatment.” From this search, 189 articles were initially identified, which were then submitted to selection criteria. The final sample comprised 6 articles that underwent selective, exploratory, and interpretative analysis within the scope of this study.